The births, lives, and deaths of corporations in late Imperial Russia - Amanda Gregg; Steven Nafziger (Bank of Finland, Institute for Economies in Transition (BOFIT), 2020)
Enterprise creation, destruction, and evolution support the transition to modern economic growth, yet these processes are poorly understood in industrializing contexts. We investigate Imperial Russia's industrial development at the firm-level by examining entry, exit, and persistence of corporations. Relying on newly developed balance sheet panel data from every active Russian corporation (N > 2500) between 1899 and 1914, we examine the characteristics of entering and exiting corporations, how new entrants evolved, and the impact of founder identity on subsequent outcomes. Russian corporations operated flexibly and competitively, conditional on overcoming distortionary institutional barriers to entry that slowed the emergence of these leading firms in the Imperial economy
URN:NBN:fi:bof-202012142558
Keywords: L11; N13; N63; O14; O16; 330; entry and exit; firm dynamics; Imperial Russia; corporations; industrialization